2021
DOI: 10.1016/j.mayocp.2020.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Community-Engaged Approaches for Minority Recruitment Into Clinical Research: A Scoping Review of the Literature

Abstract: Underrepresentation of racial and ethnic minority populations in clinical research persists in the United States, highlighting the unmet ideals of generalizability and equity of research findings and products. Previous systematic reviews exploring various facets of this phenomenon concluded that community engagement with minority groups may effectively promote recruitment and retention, but the ways in which community-engaged approaches have been used for recruitment have not been examined. We performed a scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 100 publications
1
62
0
Order By: Relevance
“…Nevertheless, our findings as to challenges and benefits corroborate and align with existing research that participatory approaches can provide benefits particularly to the recruitment and retention of trial participants. [64][65][66][67] Challenges associated with participatory research that are previously reported and complementary to our findings often involve methodological challenges around collecting, interpreting and disseminating research. 64 66 We found, similar to previous reviews, that the extent of engagement and involvement of non-academic stakeholders is highly varied, and that research that is expressly participatory is often limited.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, our findings as to challenges and benefits corroborate and align with existing research that participatory approaches can provide benefits particularly to the recruitment and retention of trial participants. [64][65][66][67] Challenges associated with participatory research that are previously reported and complementary to our findings often involve methodological challenges around collecting, interpreting and disseminating research. 64 66 We found, similar to previous reviews, that the extent of engagement and involvement of non-academic stakeholders is highly varied, and that research that is expressly participatory is often limited.…”
Section: Discussionsupporting
confidence: 66%
“…Other approaches include tabling (have a table in public locations staffed by racially concordant research staff to enroll patients), community outreach, and partnering with BIPOC community leaders and businesses, churches, and other community organizations. [11] While typically recommended to improve the enrollment of BIPOC populations in clinical trials, these approaches apply to trials that recruit participants directly and were not available to us and are generally less applicable to practice-based trials mediated by clinicians and healthcare services. For these trials, however, it may be more effective to modify trial funding and allocation of funds to speci c sites caring for BIPOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the FBOs, CBOs, and PHHS agencies were the focal point of the project. These organizations had the ability to integrate their knowledge of the local culture to maximize outreach efforts [ 23 ]. As a result, this eliminated the barrier of lack of trust that vulnerable populations have expressed concerning health research participation [ 15 , 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%